Isotopes in Condensed Matter - G. Plekhanov, Vladimir (Springer Series in Materials Science, 2013)
This book provides a concise introduction to the newly created sub-discipline of solid state physics isotopetronics. The role of isotopes in materials and their properties are describe  in this book. The problem of the enigma of the atomic mass in microphysics is briefly discussed.  The range of the applications of isotopes is wide: from biochemical process in living organisms to modern technical applications in quantum information. Isotopetronics promises to improve nanoelectronic and optoelectronic devices. With numerous illustrations this book is useful to researchers, engineers and graduate students.